2019
DOI: 10.1016/j.jses.2019.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Increased reoperation rates among patients undergoing shoulder arthroscopy with concomitant biceps tenodesis

Abstract: BackgroundThe purpose of this study was to determine whether patients undergoing any shoulder arthroscopic procedure with concomitant biceps tenodesis have higher reoperation and complication rates vs. patients undergoing shoulder arthroscopy without concomitant biceps tenodesis.MethodsA large database was queried for patients undergoing shoulder arthroscopy, identified by Current Procedural Terminology code. Only records indicating the laterality of the procedure were included. Patients were divided into 3 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…21 Biceps tenodesis techniques differ by approach (open vs arthroscopic), location (proximal, suprapectoral, subpectoral), and fixation type (soft tissue to soft tissue vs soft tissue to bone). [22][23][24][25][26] Although functional and clinical outcomes following BT with or without RCR repair are favorable, 24,[27][28][29] concerns remain about the cost effectiveness of BT over the long-term. Arthroscopic BT has been shown to have increased costs when compared with open procedures, 30 but few data exist regarding the cost-effectiveness of arthroscopic BT alone or in combination with acro when examining total procedural and postoperative costs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…21 Biceps tenodesis techniques differ by approach (open vs arthroscopic), location (proximal, suprapectoral, subpectoral), and fixation type (soft tissue to soft tissue vs soft tissue to bone). [22][23][24][25][26] Although functional and clinical outcomes following BT with or without RCR repair are favorable, 24,[27][28][29] concerns remain about the cost effectiveness of BT over the long-term. Arthroscopic BT has been shown to have increased costs when compared with open procedures, 30 but few data exist regarding the cost-effectiveness of arthroscopic BT alone or in combination with acro when examining total procedural and postoperative costs.…”
mentioning
confidence: 99%
“…Although functional and clinical outcomes following BT with or without RCR repair are favorable, 24 , 27 , 28 , 29 concerns remain about the cost effectiveness of BT over the long-term. Arthroscopic BT has been shown to have increased costs when compared with open procedures, 30 but few data exist regarding the cost-effectiveness of arthroscopic BT alone or in combination with acro when examining total procedural and postoperative costs.…”
mentioning
confidence: 99%
“… 23 2014 Japan Single Center 2011 – 2013 4 Case-control study 61 71.4 175 10 (5.714) 1 (0.571) 10 (5.714) Xiao et al. 83 2019 USA PearlDiver 2007 – 2017 3 Non-randomized controlled cohort study NR 53.59 58,907 NR NR 45 (0.076) Yeung et al. 84 2020 USA ABOS 2012 – 2016 4 Case-series 56.27 62.6 1725 2 (0.116) 3 (0.174) 5 (0.29) Rees et al.…”
Section: Resultsmentioning
confidence: 99%
“… 5 There remains a lack of consensus regarding the best treatment option for addressing LHBT-related pain, especially in patients with concomitant rotator cuff pathology. 6 Current treatment options for LHBT-related pain include nonsurgical management, tenotomy, or tenodesis. 7 A comparison between tenotomy and tenodesis has shown mixed results, with similar outcomes reported for both procedures.…”
mentioning
confidence: 99%
“… 15 Nonetheless, previous research has shown mixed results. Some studies have shown higher revision surgery rates in patients undergoing RCR with BT compared with patients undergoing RCR without BT, 6 , 15 whereas others have shown no difference in revision surgery rates at all. 16 However, these studies were limited to a 1- to 2-year postoperative period.…”
mentioning
confidence: 99%